Building a Successful Massive Open Online Course About Multiple Sclerosis: A Process Description - Claflin, Suzi B; Gates, Rachael; Maher, Maree; Taylor, Bruce V (JMIR Publications, 2020)
BackgroundOver the course of a year, we developed and tested a 6-week massive open online course (MOOC) on multiple sclerosis (MS) in consultation with the MS community. The course targeted the MS community and interested laypeople and was titled Understanding MS. The primary purpose of the course was to improve MS knowledge, health literacy, and resilience among participants. The final version of the MOOC made available for open enrollment was ranked first among all MOOCs released in 2019 (n>2400) based on participant reviews. ObjectiveThe aim of this study was to present a detailed description and assessment of the development process of the Understanding MS MOOC. MethodsThe development process included a course development focus group; the creation of more than 50 content videos and related text, quizzes, activities, and discussion prompts; the creation of original images and animations; a pilot study; and collaborations with people living with MS, MS nurses, allied health care practitioners, and neurologists and researchers from 4 universities. ResultsOverall, the process was efficient and effective. With a few small changes, we recommend this approach to those seeking to develop a similar course. This process led to the development of a highly reviewed MOOC with excellent user satisfaction. ConclusionsWe identified 5 key lessons from this process: (1) community support is essential, (2) stakeholder involvement improves content quality, (3) plan for research from the beginning, (4) coordination between the academic lead and project manager team ensures a consistent voice, and (5) a network of collaborators is a key resource.